2021
DOI: 10.1002/ange.202106216
|View full text |Cite
|
Sign up to set email alerts
|

Aluminium‐Catalyzed C(sp)−H Borylation of Alkynes

Abstract: Historically used in stoichiometric hydroalumination chemistry, recent advances have transformed aluminium hydrides into versatile catalysts for the hydroboration of unsaturated multiple bonds. This catalytic ability is founded on the defining reactivity of aluminium hydrides with alkynes and alkenes: 1,2‐hydroalumination of the unsaturated π‐system. This manuscript reports the aluminium hydride catalyzed dehydroborylation of terminal alkynes. A tethered intramolecular amine ligand controls reactivity at the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 51 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…Using an ambiphilic aluminium precatalyst, (Me 2 N)C 6 H 4 AlMe 2 , Thomas et al were able to shut down hydroalumination by the alane and catalyse the C-H borylation of terminal alkynes with HBpin (Scheme 21) [96]. Through kinetic analysis, it was found that the rate of the alkynyl-Bpin product formation was fastest during catalyst activation, rather than during catalysis, leading to an in-depth investigation of catalyst activation using variable time normalisation analysis (VTNA) and kinetic isotope effects.…”
Section: Aluminium Catalysismentioning
confidence: 99%
“…Using an ambiphilic aluminium precatalyst, (Me 2 N)C 6 H 4 AlMe 2 , Thomas et al were able to shut down hydroalumination by the alane and catalyse the C-H borylation of terminal alkynes with HBpin (Scheme 21) [96]. Through kinetic analysis, it was found that the rate of the alkynyl-Bpin product formation was fastest during catalyst activation, rather than during catalysis, leading to an in-depth investigation of catalyst activation using variable time normalisation analysis (VTNA) and kinetic isotope effects.…”
Section: Aluminium Catalysismentioning
confidence: 99%
“…9 Cowley and Thomas and co-workers recently reported an interesting application of an organoaluminium hydride catalyst for this dehydrogenative boration reaction. 10 Meanwhile, the 1,1-diboration of terminal alkynes could be promoted by Chirik's Co-catalyst, 11 Engle's Cu-catalyst 12 or Ingleson's Zn-catalyst 13 systems. If the terminal alkynes were in conjugation with an electron-withdrawing moiety, the reaction could also be promoted by Brønsted bases.…”
mentioning
confidence: 99%